Art, Murals, and Student Engagement in the Transformation of Educational Environments (Architecture Image Studies, 2025)
Murals are a powerful form of artistic expression, providing a dynamic platform for community engagement, creative exploration, and the transformation of physical spaces. In educational institutions, murals can encourage collaboration, enhance student engagement, and promote institutional identity. This study investigates the impact of mural art initiatives at the University of Applied Sciences in Ferizaj, focusing on their role in enriching the campus environment, fostering teamwork, and improving student relationships. The findings highlight the potential of murals to create inclusive, inspiring, and engaging academic spaces. By using a survey in our research process, we will analyze data from over 100 surveyed students to reveal how this creative endeavor has influenced their daily educational activities. Additionally, throughout the study, we will explore the relationships between students and between students and the institution based on the artistic initiatives of the University of Applied Sciences in Ferizaj.